Microwave-induced covalent functionalization of few-layer graphene with arynes under solvent-free conditions. Issue 17 (15th January 2018) - Sulleiro, M. V.; Quiroga, S.; Peña, D.; Pérez, D.; Guitián, E.; Criado, A.; Prato, M.
Abstract : A fast and efficient non-conventional modification of exfoliated few-layer graphene with different arynes under microwave irradiation and solvent-free conditions. Abstract : A non-conventional modification of exfoliated few-layer graphene (FLG) with different arynes under microwave (MW) irradiation and solvent-free conditions is reported. The described approach allows reaching fast, efficient and mild covalent functionalization of FLG.